Reacción de hipersensibilidad inmediata aguda durante la terapia con antiveneno F(ab’)2 por envenenamiento grado II por serpiente de cascabel: reporte de caso en México - Georgina Flores Martini; Juan Carlos Borrego Moreno; Ana Elizabeth de la Cruz Reyes; Blanca Idalia Cardiel Méndez; Ernesto Deloya Tómas; Elizabeth Guadalupe Haro Cruz; Maria Julieta Cárdenas de Luna (Critical Care & Emergency Medicine, 2026)
Rattlesnake envenomation remains a relevant cause of morbidity in Mexico, and antivenom is still the specific treatment of choice. We report the case of a 35-year-old man with grade II rattlesnake envenomation affecting the left hand, initially managed with six vials of equine polyvalent F(ab’)2 antivenom, analgesia, local supportive care, and serial clinical and laboratory monitoring. Approximately 30 minutes after antivenom administration, he developed fever, generalized pruritus, urticaria, and mild dyspnea, without hypotension, active bleeding, neurologic deterioration, or objective evidence of systemic venom progression. The event was interpreted as an acute immediate hypersensitivity reaction related to antivenom therapy. Symptom-directed treatment with antihistamines and corticosteroids was given, and antivenom was temporarily withheld for 24 hours. Because local edema persisted, antivenom was reintroduced under close monitoring and was well tolerated. The patient was readmitted one week later because of persistent edema, received additional antivenom according to clinical judgment, and showed favorable progression. This case highlights the importance of distinguishing venom progression from treatment-related hypersensitivity to support safe continuation of specific therapy when still clinically indicated.